Effect of the environment inside and outside the cage on the activity and behaviour test performance of silver foxes - Rekilä, Teppo; Ahola, Leena; Mononen, Jaakko; Harri, Mikko (Agricultural Research Centre of Finland, 1998)
Tutkimuksessa selvitettiin kasvatushäkin ympäristön vaikutusta hopeakettujen käyttäytymiseen niiden omassa häkissä ja avokenttätestissä. Hyllyn lisääminen häkin sisälle lisäsi hopeakettujen vuorokausiaktiivisuutta. Sen sijaan pesäkopin tarjoaminen ei lisännyt aktiivisuutta. Eläinhallin ulko-oven läheisyyteen sijoitetut hopeaketut olivat työpäivän aikaan passiivisempia ja illan aikana aktiivisempia kuin hallin takaosaan sijoitetut. Avokenttäkäyttäytyminen ei riippunut häkin sijainnista hallissa, eikä myöskään häkin sisällöstä. Tulosten perusteella voidaan todeta, että häkki tai häkin sisältö vaikuttivat hopeakettujen käyttäytymiseen hyvin vähän. Häkin ympäristö tulee ottaa nykyistä enemmän huomioon, kun hopeakettujen kasvatusympäristöä pyritään parantamaan.

On the basis of daily activity in the home cage and the open field test the effect of the internal design and location of cages on the behaviour of silver foxes (Vulpes vulpes) during a growth period was evaluated. The inclusion of platforms in cages increased the daytime activity of silver foxes in their home cage, but the inclusion of nest boxes did not. Silver foxes housed at the front of the animal barn were less active during the working day and more active in the evening than were animals housed at the rear. The results of the open field test did not differ significantly between animals housed in cages differing in design. This study demonstrates that the behaviour of silver foxes was only minimally affected by the interior environment of the cage, and that attempts to improve housing design should also take the environment outside the cage into account.
Keywords: Ko; turkiseläimet; ketut; tarhat; hopeakettu; eläinten käyttäytyminen; cage environment; circadian rhythm; farm foxes; open field behaviour